State of the Field: The Need for Self‐Report Measures of Health and Quality of Life for People With Intellectual and Developmental Disabilities. Issue 4 (18th June 2021) - Shogren, Karrie A.; Bonardi, Alexandra; Cobranchi, Chelsea; Krahn, Gloria; Murray, Alexa; Robinson, Ann; Havercamp, Susan M.; ,
Abstract: Background: Collecting self‐reported health and quality of life (QoL) outcomes is increasingly considered best practice, but people with intellectual and developmental disabilities (IDD) are often excluded from patient‐reported outcome measures. Objective: This article provides a literature‐informed overview of the state of the field of self‐reporting of physical health and QoL in research with adults with IDD. Approach: We first identified and synthesized definitions of key constructs related to the self‐reporting of health. Next, we summarize literature on existing and emerging practices focused on health and QoL assessment, discussing the frequent and sometimes overly broad use of proxy‐respondents in the IDD field. We then highlight emerging directions focused on cognitive accessibility and universal design. Finally, we provide conclusions and recommendations for the field. Conclusions: Informed by the literature, we provide action steps to guide the field in considering how to incorporate self‐reporting of health outcomes by people with IDD in research, policy, and practice.